2022
DOI: 10.1111/1471-0307.12847
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal properties of whey fermented by lactic acid bacteria in films for the preservation of cheese slices

Abstract: Fungal deterioration by Penicillium species in refrigerated storage conditions is one of the main risk factors for health issues and food waste in the dairy industry. The purpose of this study was to evaluate the antifungal properties of a plastic film carrying whey fermented by lactic acid bacteria (LAB). The results evidenced that a film containing whey fermented using lactic acid bacteria inhibited the growth of Penicillium commune, Penicillium verrucosum and Penicillium solitum for 23, 20 and 17 days, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The number of studies using antifungal LAB strains in films is quite limited, especially in relation to cheese products. Dopazo et al [ 35 ] reported an effective reduction with a polyvinyl alcohol (PVOH) film containing cell-free fermented whey of L. plantarum , with an extension of the shelf life of cheese slices by 15 days for samples contaminated with P. commune , by 13 days for samples contaminated with P. verrucosum , and by 14 days for samples contaminated with P. solitum . Guimarães et al [ 46 ] observed complete inhibition of P. nordicum after 30 days of storage by applying films of whey protein concentrate containing L. buchneri to cheese, but these authors used a 30% concentration of the strain LAB compared to a 10% concentration of L. brevis SJC120 used in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of studies using antifungal LAB strains in films is quite limited, especially in relation to cheese products. Dopazo et al [ 35 ] reported an effective reduction with a polyvinyl alcohol (PVOH) film containing cell-free fermented whey of L. plantarum , with an extension of the shelf life of cheese slices by 15 days for samples contaminated with P. commune , by 13 days for samples contaminated with P. verrucosum , and by 14 days for samples contaminated with P. solitum . Guimarães et al [ 46 ] observed complete inhibition of P. nordicum after 30 days of storage by applying films of whey protein concentrate containing L. buchneri to cheese, but these authors used a 30% concentration of the strain LAB compared to a 10% concentration of L. brevis SJC120 used in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Many types of polymeric materials have been used in the development of edible films and coatings with various functional properties, especially as effective carriers for bioactive compounds [ 31 , 32 , 33 ]. Among the various formulations, collagen (gelatin) and whey proteins have been widely used for incorporating live bacteria such as LAB into edible packaging [ 32 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding whey, direct effects in crop protection have been demonstrated (Pscheidt and Kenyon, 2004;Al-Mughrabi, 2007;Bettiol et al, 2008;Abdelbacki et al, 2010;Savocchia et al, 2011, Al-Razaq, 2019Ntalli et al, 2019;Garg and Kumhar, 2020;Kamel and Afifi, 2020;Muley and Singhal, 2020;Salih and Khrbeet, 2020;Illueca et al, 2021;Shachai and Khrbeet, 2021;Tripathi et al, 2021). Indirect effects are also described via the formation of biofilms (Dopazo et al, 2022;Lopusiewicz et al, 2020) or by maintaining healthier crops (Caballero et al, 2020). All these positive effects have less environmental impacts than chemicals (Gadino et al, 2010;Gadino et al, 2011).…”
Section: Wheymentioning
confidence: 99%
“…Chitosan [ 46 ], lactic and propionic acids, chitooligosaccharides [ 47 ], and enterocins [ 48 ] were also evaluated in whey-based films. Several authors used previously fermented CW to produce edible films as carriers of lactic acid bacteria [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ] or probiotics [ 56 ]. Finally, other research works refer to the proteins and peptides with biological activity present in CW films [ 57 ].…”
Section: Introductionmentioning
confidence: 99%